Pendampingan dan Pembinaan Kegiatan Baca Tulis Al Qur’an di Musholah Baitul Maghfiroh Desa Mekarjaya - Syafiatun Nabila; Fitria Zulfa; Nour Kholid; Yuliana Yuliana; Lusi Safitri (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This community service activity through mentoring and fostering Qur'an literacy activities is important in supporting the development of one's Qur'an literacy skills. Research and field practice show that ongoing effective mentoring can help children to gain a better understanding of the content of the Qur'an. The main focus of this mentoring and guidance is to improve the ability to read and write the Qur'an thoroughly and accurately, as well as ensure a deep understanding of the meaning and context of the verses of the Qur'an. This mentoring and coaching involves various methods and techniques, such as the use of interactive approaches, repetitive exercises, the use of educational technology, and the strengthening of tajweed skills. The ultimate goal of this mentoring and coaching is to create a learning environment that supports, motivates, and strengthens the individual's spiritual connection with the Qur'an, thus fostering continuous personal growth and strong character development in accordance with Islamic teachings